Immunmedierad hemolytisk anemi hos hund - Voudinmäki, Mirja (2007)
Immune-mediated haemolytic anaemia (IMHA) is an immune-mediated destruction of erythrocytes and is one of the most common haematological diseases diagnosed in dogs. The haemolysis is a type II immunoreaction and is initiated by IgG or IgM antibodies or complements.